Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang Sayuran Di Pasar Pinasungkulan Karombasan Kota Manado - Londa, Armando Alexander; Porajouw, Oktavianus; Manginsela, Elsje Pauline (Sam Ratulangi University, 2023)
The purpose of this study is to analyze the factors that influence the income of vegetable traders in the Pinasungkulan Karombasan market. The type of data in this study is primary data obtained directly from interviews and through questionnaires distributed to respondents, namely vegetable traders at the Pinasungkulan Karombasan market, and also through secondary data from previous research journals. The number of samples in this study amounted to 37 respondents with a census technique according to direct observation during the pre-survey. The results of this study indicate the factors that influence the income of vegetable traders in the Pinasungkulan Karombasan market, namely capital, level of education, length of business and hours of work. Factors that significantly influence are capital and working hours. The level of education and length of business have no significant effect on the income of vegetable traders at the pinasungkulan karombasan market, Manado City.